2020
DOI: 10.1016/j.mechmat.2020.103361
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic multiscale modeling of the thermomechanical behavior of polycrystalline shape memory alloys

Abstract: A multi-scale model simulating hysteretic thermomechanical behavior of polycrystalline shape memory alloys (SMA) is presented. Using a kinetic Monte-Carlo approach, the energybased model estimates the stochastic average in terms of volume fraction for a phase or phase variant deriving from the Gibbs free energy density as a selection inside a given population. Indeed pseudo-elastic behavior for example is well-known to be associated with the nucleation of martensite plates inside the austenite parent phase. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…5, a series of raw spectra D(2, y) are obtained, each of which is composed of the three phases of NiTinol: A, M and R. For the proper identification of these phases, it is possible to prepare the specimen to obtain pure A and M phases with either a load-free state at high temperature (austenite) or under load after a full transformation (martensite), with a representative anisotropy along the tensile axis due to the selection of variants. However, this is not the case for the R phase: in a previous study (Chang et al, 2020), by conducting differential scanning calorimetry (DSC) over the NiTinol specimen, it was shown that the R phase is present only in the intermediate stages and never uniformly.…”
Section: Spatial Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…5, a series of raw spectra D(2, y) are obtained, each of which is composed of the three phases of NiTinol: A, M and R. For the proper identification of these phases, it is possible to prepare the specimen to obtain pure A and M phases with either a load-free state at high temperature (austenite) or under load after a full transformation (martensite), with a representative anisotropy along the tensile axis due to the selection of variants. However, this is not the case for the R phase: in a previous study (Chang et al, 2020), by conducting differential scanning calorimetry (DSC) over the NiTinol specimen, it was shown that the R phase is present only in the intermediate stages and never uniformly.…”
Section: Spatial Spectramentioning
confidence: 98%
“…5(a) at 2 = 49 and 92 correspond to A{110} and A{211}, respectively, which are consistent with the theoretical XRD diffractograms. The {200} peak is not visible in the experimental spectra because of the pronounced crystallographic texture of this laminated material (Chang et al, 2020). Therefore, at this stage, the collected experimental diffraction spectra are taken as the data profile for pure austenite.…”
Section: Spatial Spectramentioning
confidence: 99%
“…This calculation is complemented by a minimization process of g α regarding the direction cosines of domain families α to take the so-called magnetization rotation mechanism into account. Following this strategy, a Boltzmann function gives the solution of the stochastic approach [13] (with V 0 a reference microscopic volume, k B the Boltzmann constant (1.38 × 10 −23 J.K −1 ) and T the temperature (293 K)).…”
Section: Gibbs Free Energy and Reversible Modelingmentioning
confidence: 99%